2001
DOI: 10.1073/pnas.141226798
|View full text |Cite
|
Sign up to set email alerts
|

Xenopus Bcl-X L selectively protects Rohon-Beard neurons from metamorphic degeneration

Abstract: Amphibian metamorphosis involves extensive, but selective, neuronal death and turnover, thus sharing many features with mammalian postnatal development. The antiapoptotic protein Bcl-X L plays an important role in postnatal mammalian neuronal survival. It is therefore of interest that accumulation of the mRNA encoding the Xenopus Bcl-X L homologue, termed xR11, increases abruptly in the nervous system, but not in other tissues, during metamorphosis in Xenopus tadpoles. This observation raises the intriguing po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 48 publications
(63 citation statements)
references
References 32 publications
2
61
0
Order By: Relevance
“…The two bcl-2 family members cloned in Xenopus belong to the subfamily of cell death inhibitors [48], [49]. They are capably of inhibiting cell death when expressed in tissue culture cells or in Xenopus tadpoles.…”
Section: Cell Death Genes During Metamorphosismentioning
confidence: 99%
“…The two bcl-2 family members cloned in Xenopus belong to the subfamily of cell death inhibitors [48], [49]. They are capably of inhibiting cell death when expressed in tissue culture cells or in Xenopus tadpoles.…”
Section: Cell Death Genes During Metamorphosismentioning
confidence: 99%
“…BCL-2 and BCL-XL (xR11) are functionally identical in this assay. xR11 injection alone does not affect luciferase expression in the absence of apoptosis (Coen et al, 2001). These data show that Xenopus BCL-XL is able to antagonize tBID-induced apoptosis in vivo.…”
Section: Xenopus Xr11 the Homologue Of Mammalian Bcl-xl Counteractsmentioning
confidence: 68%
“…First, Bax expression increases as metamorphosis progresses (Sachs et al, 1997) and second, an antisense approach confirmed the implication of Bax as an actor in the mechanism of muscle loss (Sachs et al, 2004). Furthermore, XR11 can abrogate the proapoptotic effect of Bax when coexpressed in muscle (Coen et al, 2001), and muscle loss can be delayed by overexpression of XR11 during natural metamorphosis (Rowe et al, 2002). .…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations